Creating breakthrough ideas : the collaboration of anthropologists and designers in the product development industry. - Squires, Susan, ....-; Byrne, Bryan, ....- (London : Bergin and Garvey, 2002)
Explores the opportunities and challenges facing ethnographic researchers and designers who are learning to collaborate as they create breakthrough ideas.